Degree possession of secondary teachers for effective teaching skills from the perspective of the teachers themselves in the Mafraq Governorate (Journal of the College of Education for Women, 2019)
This study aimed to reveal the degree possession of secondary teachers for effective teaching skills from the perspective of the teachers themselves in the Mafraq governorate .To achieve the objective of the study(45) teachers were chosen randomly, also a questionnaire composed of 17 was prepared spread over three skill areas (planning, implementation, evaluation).After application of the tool on the sample results of the study showed that the degree of ownership ranged between medium and high.The results showed no differences in the degree of ownership due to the variables of sex in favor of females and variable qualification for the benefit of people with qualified Master higher, while differences are attributed to the experience it did not appear in the light of those the result researcher recommended the preparation of training programs based on effective teaching skills to enhance cognitive performance and performance piece for teachers and then transfer that knowledge to the impact in the classroom and the need for further studies of effective teaching skills of the other samples.Key words: teaching skills of effective secondary school teachers